2019
DOI: 10.1038/s41598-019-48150-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phenotype order in molecular data

Abstract: Biological entities are key elements of biomedical research. Their definition and their relationships are important in areas such as phylogenetic reconstruction, developmental processes or tumor evolution. Hypotheses about relationships like phenotype order are often postulated based on prior knowledge or belief. Evidence on a molecular level is typically unknown and whether total orders are reflected in the molecular measurements is unclear or not assessed. In this work we propose a method that allows a fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…This fact might sound questionable and unconventional, at first sight. However, Lattke et al [22] and Lausser et al [23] showed that an expected class structure, which is based on the meaning of classes, is not always reflected in the chosen feature space. In such classification tasks, OC-based classification models (CMs) are not able to exploit the given feature space, with respect to the assumed class order, in general.…”
Section: E Discussion -The Meaning Of Class Labelsmentioning
confidence: 99%
See 4 more Smart Citations
“…This fact might sound questionable and unconventional, at first sight. However, Lattke et al [22] and Lausser et al [23] showed that an expected class structure, which is based on the meaning of classes, is not always reflected in the chosen feature space. In such classification tasks, OC-based classification models (CMs) are not able to exploit the given feature space, with respect to the assumed class order, in general.…”
Section: E Discussion -The Meaning Of Class Labelsmentioning
confidence: 99%
“…The outcomes presented by Lattke et al [22] indicate that one can detect ordinal class structures by applying CCAs, in combination with linear SVM models. Lausser et al [23] showed that this specific approach can be used to assess phenotype order in molecular data. Such kind of data represents one of the many interesting tasks, in which we usually do not have any a priori information about the corresponding structure.…”
Section: B Cascaded Classification Architecturesmentioning
confidence: 99%
See 3 more Smart Citations